2016
DOI: 10.1038/srep24193
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteria-responsive sonic hedgehog signaling mediates programmed death-ligand 1- and prostaglandin E2-induced regulatory T cell expansion

Abstract: CD4+CD25+FoxP3+ regulatory T cells (Tregs) are exploited by mycobacteria to subvert the protective host immune responses. The Treg expansion in the periphery requires signaling by professional antigen presenting cells and in particularly dendritic cells (DC). However, precise molecular mechanisms by which mycobacteria instruct Treg expansion via DCs are not established. Here we demonstrate that mycobacteria-responsive sonic hedgehog (SHH) signaling in human DCs leads to programmed death ligand-1 (PD-L1) expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 62 publications
5
41
1
Order By: Relevance
“…This discrepancy might be due to the fact that previous report focused on active disease where prolonged infection can enhance additional co-stimulatory molecules that might not be present during the earlier phases of stimulation. For example, APCs from active disease express both the co-stimulatory molecules PD-L1 and PD-L2 (31), whereas our current data and previous reports show that DCs from healthy individuals stimulated with M. tuberculosis both at the transcript level as well as the protein level induce only PD-L1 and not PD-L2 (30, 33). It is essential to note that we have used γ-irradiated M. tuberculosis or M. tuberculosis -derived cell wall, cell membrane, or cytoplasmic fractions in our experiments, and these conditions may not completely mimic in vivo situation of infection with live bacteria.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…This discrepancy might be due to the fact that previous report focused on active disease where prolonged infection can enhance additional co-stimulatory molecules that might not be present during the earlier phases of stimulation. For example, APCs from active disease express both the co-stimulatory molecules PD-L1 and PD-L2 (31), whereas our current data and previous reports show that DCs from healthy individuals stimulated with M. tuberculosis both at the transcript level as well as the protein level induce only PD-L1 and not PD-L2 (30, 33). It is essential to note that we have used γ-irradiated M. tuberculosis or M. tuberculosis -derived cell wall, cell membrane, or cytoplasmic fractions in our experiments, and these conditions may not completely mimic in vivo situation of infection with live bacteria.…”
Section: Discussioncontrasting
confidence: 79%
“…Several recent reports have indicated that PD-1–PD-L1/PD-L2 axis has a pivotal role in the regulation of T cell response to M. tuberculosis (29, 31, 33). Therefore, to decipher the role of PD-L1/PD-L2 in regulating Th17 response to M. tuberculosis , we first investigated the ability of M. tuberculosis and its different antigen fractions in modulating PD-L1 and PD-L2 expression on monocytes and DCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we hypothesize that infection stimulates regulatory/suppressor T-cells that can favor bacterial persistence through the secretion of IL-10. A similar effect has been described during Mycobacterium tuberculosis infection where COX-2/PGE 2 axis stimulates T-reg expansion (Garg et al, 2008; Holla et al, 2016). Thereby, T-reg accumulation contributes to the decrease of bacterial clearance in infected mice (Kursar et al, 2007).…”
Section: Discussionsupporting
confidence: 68%
“…Bacteria stimulate Treg expansion by several mutually nonexclusive mechanisms. Mycobacterium tuberculosis ‐mediated Treg expansion in humans implicate PD‐1‐PD‐L1/PD‐L2 axis and COX‐2‐catalysed Prostaglandin E2 (PGE2) (Garg et al, ; Holla et al, ; Periasamy et al, ; Singh, Mohan, Dey, & Mitra, ; Trinath, Maddur, Kaveri, Balaji, & Bayry, ). Blockade of these pathways in vitro not only abrogated Treg expansion but also reciprocally enhanced IFN‐γ responses (Periasamy et al, ; Singh et al, ; Stephen‐Victor et al, ; Stephen‐Victor et al, ).…”
Section: Tregs In Bacterial Infections: Inhibition Of Protective Immumentioning
confidence: 99%